A MANAGERIAL ANALYSIS OF ECONOMIC LOSSES ATTRIBUTABLE TO SMOKING AND THE IMPLEMENTATION OF NON-SMOKING AREA POLICIES - Achmad R. Muttaqien Al-Maidin; Pupin Astuti; Akhyar Rahmatul Rohim; Mutia Nur Rahmah (Homes Journal = Hospital Management Studies Journal, 2025)
Introduction: Smoking has caused a heavy economic burden around the world. In Indonesia, in the South Sulawesi Region, smoking has become a habit. The economic losses caused by smoking have reached unreasonable limits, coupled with the increase in smoking in various regions of Indonesia, affecting the social life of the community. One of the efforts made by the Indonesian government is a policy related to Non-Smoking Areas (KTR). Methods: This study used qualitative and quantitative methods with a sample of 400 respondents from the total population of Palopo City. The qualitative method uses rapid ethnography to directly observe the habits of the people in the KTR. The quantitative method uses a survey of economic loss and community compliance with regional regulations and smoking habits in Palopo City. Results: The results show that the people of Palopo City are able to smoke an average of 14 cigarettes a day (1.70 USD), which is 420 cigarettes a month (51.06 USD), and are able to spend 5110 cigarettes (18637.99 USD) a year for one smoker. These costs are spent only on purchasing cigarettes and do not include the costs that must be paid by smokers to overcome health problems caused by smoking. This study also examines smokers' habits and their adherence to the KTR policy. Conclusion: The costs incurred for smoking in Palopo City are very high. Cost estimates can be used to evaluate cigarette tax rates and other tobacco-related policies. The habit and need for smoking are one of the factors contributing to the high costs incurred each year to buy cigarettes. The smoking habit which has a high risk of health problems and poor compliance is a challenge for the government and policy enforcers to pay more attention to this problem. To enhance the effectiveness of tobacco control, the government needs to increase cigarette taxes, strengthen the enforcement of Smoke-Free Areas (KTR), and expand public education programs on the dangers of smoking.